Respostas

A melhor resposta!
2014-04-30T17:31:16-03:00
A) x² - 3x - 4 = - 4
x² - 3x - 4 + 4 = 0
x² - 3x = 0
Δ = (- 3)² - 4 . 1 . 0               X = - (- 3) +- √9  / 2.1
Δ = 9 - 0                              X = 3 +- 3  / 2
Δ = 9
x' = 3 + 3 / 2 => 6 / 2 = 3              x" = 3 - 3 / 2 => 0 / 2 = 0

b) x² - 3x - 4 = 0
Δ = (- 3)² - 4 . 1 . (- 4)                X = - (- 3) +- √25  / 2.1
Δ = 9 + 16                                X = 3 +- 5 / 2
Δ = 25
x' = 3 + 5 / 2 => 8 / 2 = 4               x" = 3 - 5 / 2 => - 2 / 2 = - 1

c) x² - 3x - 4 = - 6
x² - 3x - 4 + 6 = 0
x² - 3x + 2 = 0
Δ = (- 3)² - 4 . 1 . 2                   X = - (- 3) +- √1  / 2.1
Δ = 9 - 8                                  X = 3 +- 1  / 2
Δ = 1
x' = 3 + 1 / 2 => 4 / 2 = 2              x" = 3 - 1 / 2 => 2 / 2 = 1


Substitua os "x" pelas raízes encontrada e tire a prova real ;)
3 5 3